The Information in Governmental Annual Reports: A Contemporaneous Price Reaction Approach - Ingram, Robert W.; Raman, K. K.; Wilson, Earl R. (The Accounting Review, 1989)
[Considerable evidence exists that governmental accounting numbers are related empirically to bond risk and return measures. However, prior research does not preclude the possibility that accounting numbers merely reflect unobserved factors such as economic and political attributes impounded in bond measures. This study considers whether governmental annual financial reports convey new information directly to the bond market. Changes in bond prices during the period around the release date of governmental annual reports were examined to assess market responses to the reports. No significant evidence was obtained to suggest that municipal bond investors use the information in the annual report at the time of its release to adjust bond prices. In contrast, new bond issues and bond rating announcements were associated with significant market reactions. Thus, these results indicate that, while issuer-specific accounting information may be used by bond investors in conjunction with decisions involving new issues and rating evaluations, investors do not appear to impound the information directly into secondary market prices at the time the information is released.]